An Evaluation Study of Kampung KB in Denpasar City with Working Partners - I Gusti Ngurah Made, Bayuningrat (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
Backgrounds: The National Population and Family Planning Agency (BKKBN) is a non-ministerial institution. The problem is that there is stagnation in program achievements and the weak implementation of the KKBPK Program. The BKKBN established the Kampung KB as a strategic innovation for the full implementation of the KKBPK Program. Methods: The goal is to know the evaluation of the establishment and implementation of the Kampung KB as a miniature family planning program, grounding, bringing services closer, actualizing 8 family functions, revitalizing KKBPK. Since it was launched in 2016, it has never been evaluated, the criteria for establishing, using Family Data Collection, participation, implementation of regional and cross-sectoral Government commitments, forms of activity, coaching and mobilization, support for facilities and infrastructure, achievement of indicators, knowledge and community participation. Results: Quantitative studies in-depth interviews are input, process, implementation, monitoring, evaluation, reporting and achievement of program success indicators. Conclusion: Careful planning so that the program runs effectively, emphasizes the quality of the Kampung KB according to the input and process, not only the quantity target. The program must refer to the needs of the community, so an analysis of community needs is important before determining the program.